Using Learning Management System , Edmodo, for Sosiolinguistic Learning: A Case Study at English Education - Eliana Nur Azizah (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
AbstractLearning in college is growing, distance is not a burden in the learning process. There are various media that can be used without having to face to face between lecturers and students. In this case the researcher examines the use of Edmodo media in the sociolinguistic learning process in English Language Education. The research method used is descriptive qualitative. The results obtained that Edmodo can provide convenience in the learning process as in the case of assignments or quizzes from lecturers. The students also felt comfortable and comfortable with the media because it was easy to use as a learning process.Keywords: Edmodo, English education